2010
DOI: 10.1007/s11627-010-9279-6
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration in oil palm using the thin cell layer technique

Abstract: An efficient procedure has been developed for inducing somatic embryogenesis and regeneration of plants from tissue cultures of oil palm (Elaeis guineensis Jacq.). Thin transverse sections (thin cell layer explants) of different position in the shoot apex and leaf sheath of oil palm were cultivated in Murashige and Skoog (MS) (Physiol Plant 15:473-497, 1962) medium supplemented with 0-450 µM picloram and 2,4-D with 3.0% sucrose, 500 mg L −1 glutamine, and 0.3 gL −1 activated charcoal and gelled with 2.5 gL −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 31 publications
2
34
1
11
Order By: Relevance
“…Furthermore, studies would be necessary with other explant sources (leaf sheaths and inflorescence) using thin cell layer explants to induce somatic embryogenesis. This technique is considered promising for somatic embryogenesis of palm species, e.g., for Elaeis guinensis (Scherwinski-Pereira et al 2010) and B. gasipaes (Steinmacher et al 2007b). The morphogenetic responses observed in this study were similar to the results reported by Guerra and Handro (1998) and Guerra et al (2000) in somatic embryogenesis of E. edulis.…”
Section: Effect Of Sucrose Concentration On In Vitro Germination Of Isupporting
confidence: 89%
“…Furthermore, studies would be necessary with other explant sources (leaf sheaths and inflorescence) using thin cell layer explants to induce somatic embryogenesis. This technique is considered promising for somatic embryogenesis of palm species, e.g., for Elaeis guinensis (Scherwinski-Pereira et al 2010) and B. gasipaes (Steinmacher et al 2007b). The morphogenetic responses observed in this study were similar to the results reported by Guerra and Handro (1998) and Guerra et al (2000) in somatic embryogenesis of E. edulis.…”
Section: Effect Of Sucrose Concentration On In Vitro Germination Of Isupporting
confidence: 89%
“…Furthermore, TCL provides a simple and efficient system of micropropagation that can be used in the propagation of elite clonal plants ( Monja-Mio & Robert 2013). In addition to A. aculeata, the TCL technique has been used with success in Bactris gasipaes (Steinmacher et al 2007c) and in Elaeis guineensis (Scherwinski-Pereira et al 2010). In both cases, the initial explants were leaf transverse TCLs of in-vitro grown seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The TCL culture may induce specific morphogenic routes, such as controlled somatic embryo production (Nhut et al 2003). The technique has proven efficient at propagating many plant species (Silva et al 2007;Silva 2010) species, has been used with peach palm (Bactris gasipaes) by Steinmacher et al (2007c) and oil palm (Elaeis guineensis), with leaf explants (Scherwinski-Pereira et al 2010) and immature inflorescences (Guedes et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Currently, genetic improvement programs for African oil palm (Elaeis guineenis) have sought the introgression of genes of interest present in germplasm from the American oil palm (Elaeis oleifera). Thus, elite plants of E. guineensis and E. oleifera have been crossed in order to obtain F1 hybrids with good productivity, shorter stature and resistance to disease (Barcelos et al, 2002;Chia et al, 2009;Scherwinski-Pereira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%